Interactive 3D architectural visualization with semantics in web browers - Książek, Marcin; Pietruszka, Maria (Wydawnictwo Politechniki Łódzkiej, 2012)
This paper focuses on rendering, and access to visual and descriptive information about the digital architectural models on the Web. It was proposed to reach these contents with a help of deep linking, which allows to access to different views and descriptions from both the internal navigation system or from the browser, or search engine. Along with the HTML5 and WebGL it allows updating the link during the exploration of a virtual model, and remembers to re-use. Although all the methods were tested on architecture's models, it can be used in other interactive 3D applications.